Ruptured popliteal cyst simulating deep vein thrombosis with false positive radiofibrinogen uptake - Gibbons, D. (1975)
A case is described in which deep vein thrombosis of the calf was initially diagnosed on the basis of the clinical signs and the radiofibrinogen uptake in a patient suffering from rheumatoid arthritis. The correct diagnosis of ruptured popliteal cyst was later established by arthrography and phlebography. Attention is drawn to the unreliability of the radiofibrinogen uptake test in the presence of ruptured popliteal cyst and alternative diagnostic methods are discussed.